2016
DOI: 10.1016/j.nrjag.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The solar activity by wavelet-based multifractal analysis

Abstract: The interest in the relation between the solar activity and climate change is increasing. As for the solar activity, a fractal property of the sunspot series was studied by many works. In general, a fractal property was observed in the time series of dynamics of complex systems. The purposes of this study were to investigate the relationship between the sunspot number, solar radio flux at 10.7 cm (F10.7 cm) and total ozone from a view of multifractality. To detect the changes of multifractality, we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Because of its capability of decomposing a signal into small fractions that are well localized in time and frequency and detecting local irregularities of a signal (areas of the signal where a particular derivative is not continuous) such as nonstationarity, oscillatory behaviour, breakdown, discontinuity in higher derivatives, the presence of long-range dependence, and other trends (Maruyama 2016b;Puckovs & Matvejevs 2012), wavelet analysis remains one of the most preferred signal analysis techniques to date. Additionally, there is a claim that wavelet transforms are suitable for multifractal analysis and allow reliable multifractal analysis to be performed (Muzy et al 1991).…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its capability of decomposing a signal into small fractions that are well localized in time and frequency and detecting local irregularities of a signal (areas of the signal where a particular derivative is not continuous) such as nonstationarity, oscillatory behaviour, breakdown, discontinuity in higher derivatives, the presence of long-range dependence, and other trends (Maruyama 2016b;Puckovs & Matvejevs 2012), wavelet analysis remains one of the most preferred signal analysis techniques to date. Additionally, there is a claim that wavelet transforms are suitable for multifractal analysis and allow reliable multifractal analysis to be performed (Muzy et al 1991).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…In addition, Belete et al (2018a) verified that redshift correction does not affect quasars' multifractality behaviour, which is the same in both the observed and rest frames of quasars. Multifractality analysis has been applied in different science cases (e.g., Maruyama et al 2017;Maruyama 2016a;Kasde et al 2016;Agarwal et al 2016;de Freitas et al 2016;Aliouane & Ouadfeul 2013;Jagtap et al 2012;Ouahabi & Femmam 2011;Nurujjaman et al 2009;Lin & Sharif 2007;Degaudenzi & Arizmendi 1998). Our work is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous wavelet transform is an excellent tool for mapping the changing properties of nonstationary signals. Because of its capability of decomposing a signal into small fractions that are well localized in time and frequency and of detecting local regularities of a signal (areas on the signal where a particular derivative is not continuous) such as nonstationarity, oscillatory behavior, breakdown, discontinuity in higher derivatives, the presence of long-range dependence, and other trends, wavelet analysis remains one of the most preferable signal analysis techniques to date (Maruyama 2016 ;Andrejs Puckovs & Andrejs Matvejevs 2012 ). These strengths of wavelet transform make it preferable to other traditional singularity analysis techniques, and there is a claim that it is suitable for multifractal analysis and allows for reliable multifractal analysis to be performed Muzy & Arneodo (1991 ).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Most astrophysical objects are possibly associated with continuous nonlinear stochastic systems due to their complexity in nature. A fractal behavior can be observed in the time series of complex systems (Maruyama 2016 ). It has been shown that quasars, in general, are among complex systems that have nonlinear time series characterized by fractal behavior ( Vio 1991 ) and also by sudden bursts of very large amplitude (Barbieri 1990 ;Kidger 1989 ), which implies that the dynamical evolution of quasars is nonlinear (i.e., described by nonlinear stochastic differential equations) ( Vio 1991 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation